DEVELOPMENT OF PJBL STEM-BASED PHYSICS E-MODULES IN IMPROVING GENERIC SCIENCE SKILLS OF YPPK TERUNA BAKTI JAYAPURA CLASS X IPA STUDENTS IN THE MATERIAL OF VECTOR ANALYSIS IN PARABOLA MOTION - Albert Lumbu; Victoria Dian Pratami Kurniawan (Jurnal Ilmu Pendidikan Indonesia, 2023)
This study aims to determine the feasibility of developing PjBL STEM-based Physics e-modules and improving students' generic science skills (KGS) using PjBL STEM-based Physics e- modules on vector analysis materials on parabolic motion. The research method used is R&D (Research and Development). The research sample consisted of 24 students. The results showed that the feasibility of the PjBL STEM-based Physics e-module on vector analysis material on parabolic motion obtained an average percentage of 92% with a very suitable category for use as a teaching material. Generic science skills (KGS) of class X IPA students on vector analysis material on parabolic motion resulted in an average percentage of 47.92% in the less skilled category before using the PjBL STEM-based physics e-module and resulted in an average percentage of 82.16% in the skilled category after using the PjBL STEM-based physics e-module